Pengaruh Lama Penyimpanan Rimpang Kunyit (Curcuma domestica Vahl) Terhadap Daya Hambat Antioksidan - Suparmajid, Armin H.; Sabang, Sri Mulyani; Ratman, Ratman (Universitas Tadulako, 2016)
The research about the effect of storage time of tumeric (curcuma domestica vahl) for inhibition of antioxidant has been conducted. The study aims to determine the effect of storage time of tumeric (curcuma domestica vahl) for inhibition of antioxidants as well as to determine how much inhibition of antioxidant found in tumeric. This study used a variation of storage time namely 8, 13 and 18 days. The extract of tumeric was obtained by maceration method using ethanol. The antioxidant activity of turmeric was measured by UV Vis spectrophotometry in which DPPH (1,1-difenil-2-pikrilhidrazil) as a reagent. The absorbance measurements was carried out at a wavelength of 517 nm to determine the percentage of inhibition of antioxidant in turmeric and vitamin C (as a positive control). The results revealed that percentage of inhibition of vitamin C is 56.68%, while the percentage of inhibition of turmeric decrease during storage. Based on the data obtained, turmeric with storage time of 8 days is 43.96%, turmeric with storage time of 13 days is 23.27%, and turmeric with storage time of 18 days is 11.92%. This study showed that the effect of storage time on the inhibition of antioxidant turmeric are characterized by a decrease of percentage inhibition of antioxidants in turmeric during the storage period.